Reflexiones acerca de un concurso - Romero, Mauro (1999)
Banco Central de la República Argentina, Reconquista 250, Buenos Aires
Keywords: CONCURSOS; PREMIOS; BANCOS; ARQUITECTURA BANCARIA; ARGENTINA; BUENOS AIRES